2018
DOI: 10.3892/mmr.2018.8473
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin alleviates post-resuscitation myocardial dysfunction in rats potentially through increasing the expression of angiotensin II receptor type 2 in myocardial tissues

Abstract: Activation of renin-angiotensin system (RAS) is one of the pathological mechanisms associated with myocardial ischemia-reperfusion injury following resuscitation. The present study aimed to determine whether erythropoietin (EPO) improves post-resuscitation myocardial dysfunction and how it affects the renin-angiotensin system. Sprague-Dawley rats were randomly divided into sham, vehicle, epinephrine (EP), EPO and EP + EPO groups. Excluding the sham group, all groups underwent cardiopulmonary resuscitation (CPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Studies have found that the expression of AT1R is significantly upregulated in the myocardial tissues of CA-CPR-ROSC rats and that the expression of AT2R is relatively increased, which is one of the mechanisms of myocardial dysfunction after ROSC. 13 In CA-CPR-ROSC rats, Ang (1-7) can upregulate MasR expression and improve cardiac function after resuscitation. 12 In the current study, we investigated the time-dependent alterations in ATR expression and found that the expression of AT2R, MasR, and especially AT1R increased gradually in the myocardial tissues of rats at 2, 4, and 6 hours after ROSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that the expression of AT1R is significantly upregulated in the myocardial tissues of CA-CPR-ROSC rats and that the expression of AT2R is relatively increased, which is one of the mechanisms of myocardial dysfunction after ROSC. 13 In CA-CPR-ROSC rats, Ang (1-7) can upregulate MasR expression and improve cardiac function after resuscitation. 12 In the current study, we investigated the time-dependent alterations in ATR expression and found that the expression of AT2R, MasR, and especially AT1R increased gradually in the myocardial tissues of rats at 2, 4, and 6 hours after ROSC.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Previous studies have found that the greater the increase in Ang Ⅱ expression in a rat model of CA and the sera of patients with CA, the more severely cardiac function is impaired. 12,13 Moreover, research has revealed that knockout of the angiotensinconverting enzyme-2 gene in rats decreases the level of Ang (1)(2)(3)(4)(5)(6)(7), increases the level of Ang II, and aggravates myocardial infarction. 14 In vitro and in vivo experiments have shown that knockout of the Mas gene in mice decreases left ventricular filling pressure, LVdp/dtmax, cardiac output, and the cardiac index.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Ang II may exert immune system modulation[ 33 ] and/or direct anti plasmodium activity[ 34 ]. The subsequently increased local tissue EPO levels would thus bypass systemic EPO prothrombotic effects while possibly also conferring the demanded tissue protection[ 35 ] and mitigation against Plasmodium invasion[ 12 , 26 , 32 ]. Significantly higher age-related ACE activities in serum are found in newborns and premature infants as well as healthy children and teenagers than adults [ 36 ].…”
Section: Young Age and Epo Augmenting Genetic Determinants: Evolutionary Lessons On How To “Save The Children”mentioning
confidence: 99%